Effect of angiotensin-converting enzyme inhibitors and/or angiotensin II receptor blockers on the pathophysiology and therapeutics of experimental COVID-19 - Santos, Yasmin da Silva (2024)
In December 2019, cases of pneumonia of unknown origin emerged in China, presenting with fever, cough, and respiratory difficulty, and the syndrome was later named COVID-19. SARS-CoV-2, the etiological agent of COVID-19, infects human cells through the spike protein, which binds to angiotensin-converting enzyme 2 (ACE2), responsible for blood pressure regulation and expressed in various tissues, including the lungs, heart, and kidneys. Medications such as ACE inhibitors (ACEi) and angiotensin II receptor blockers (ARBs) regulate the levels of angiotensin II (pro-inflammatory) and angiotensin 1-7 (anti-inflammatory) and can modulate the expression of ACE2. The increase in ACE2 induced by ACEi and/or ARBs during a SARS-CoV-2 infection could, on one hand, lead to increased viral load and, therefore, severity, or, on the other hand, result in better vascular homeostasis, with less vasoconstriction and thrombosis and, therefore, a more favorable outcome. Thus, this study investigates how treatment with ACEi, ARBs, or a combination of both affects ACE2 expression, lung damage, and outcomes in COVID-19. K18-hACE2 mice, treated or not with ACEi and/or ARBs, administered orally through flavored gelatin (10 mg/Kg/day), were infected with 10∧5 PFU of SARS-CoV-2. Untreated infected animals exhibited clinical manifestations such as lethargy, weight loss, and reduced lung capacity, culminating in death 5-9 days post-infection (dpi). The infection reduced pulmonary ACE2 levels at 3 and 5 dpi and induced a strong increase in proinflammatory cytokine expression at 6-7 dpi. Animals treated with lisinopril showed increased ACE2 in the lungs after 21 days of treatment and a rapid reversal of the post-infection ACE2 drop. These animals had higher viral loads in the lungs but a strong decrease in pro-inflammatory cytokine expression. Lisinopril treatment did not alter weight loss, clinical scores, respiratory capacity loss, histopathological findings, or mortality induced by experimental COVID-19. However, the use of lisinopril + losartan improved clinical symptoms, lung function, and also reduced cytokine levels, despite also increasing viral load. Treatment with losartan alone improved the ACE1/ACE2 axis balance and did not lead to increased viral load. None of the treatments altered the survival of infected animals. Overall, the treatments presented deleterious effects (increased viral load in the lungs) that were offset by beneficial effects (decreased proinflammatory response), leading to marginal benefits for the treated mice.